2021
DOI: 10.1108/ijbpa-05-2021-0068
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BIM-related factors affecting construction project performance

Abstract: PurposeThis study aims to investigate the impact of primary building information modelling (BIM)-related factors, extracted from the literature on the subject, on construction project performance.Design/methodology/approachBased on data collected from 134 BIM users, this study used structural equation modelling to assess the impact of these factors in five main BIM-related factor clusters.FindingsThe results of the analysis confirmed the reliability and validity of the research design and outcomes. The finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…This cluster was extracted from flowing critical success factors that are competitive process to select sub-contractors, an efficient private approval process, an efficient sub-contractors approval process, appropriate evaluation standards, competitive procurement process, transparency in the procurement process, transparency process to select sub-contractors. PPP is a procurement process, therefore there is a need for transparency throughout this process and it does not only apply to the tendering process but must be observed throughout the delivery of the PPP projects [47,54,58]. The information and reports on the PPP projects should be made publicly available and Parties should openly consult each other for any clarification on the projects' delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This cluster was extracted from flowing critical success factors that are competitive process to select sub-contractors, an efficient private approval process, an efficient sub-contractors approval process, appropriate evaluation standards, competitive procurement process, transparency in the procurement process, transparency process to select sub-contractors. PPP is a procurement process, therefore there is a need for transparency throughout this process and it does not only apply to the tendering process but must be observed throughout the delivery of the PPP projects [47,54,58]. The information and reports on the PPP projects should be made publicly available and Parties should openly consult each other for any clarification on the projects' delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In order to lead the success of the implementation of PPP infrastructure projects, several failure or success factors of a PPP project have been determined by numerous studies. Since the 1990s, studies on CSFs of PPP projects have been conducted by studies to identify key success factors to find out the best ways of implementing PPP policy for infrastructure development [31,54,58]. CSFs defined as the 'few key areas of activity where favorable results are absolutely necessary for a manager to reach his/her goals' [49].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…2.1.2 Client's request. The most frequently identified obstacle in all types of professions is the lack of client demand (Almuntaser et al, 2018;Ayinla and Adamu, 2018;Georgiadou, 2019;Van Tam et al, 2021). The construction sector was unprepared to adopt BIM.…”
Section: Barriers Of Building Information Modelling Implementationmentioning
confidence: 99%
“…It has also been widely reported that any financial problem regardless of reason leads to payment delay and therefore causes delay in project schedule [24]. The financial status of stakeholders is a top critical factor affecting the construction labor productivity based on the study carried out by [25]. This is due to large amount of capital required to cover daily project execution expenses.…”
Section: Respondents' Perception On Common Risk Factorsmentioning
confidence: 99%